Love and fashion: musical comedy and Yugoslav dolce vita. Issue 2 (4th May 2019) - Buhin, Anita
Abstract: As the first Yugoslav musical comedy, the film Ljubav i moda/Love and fashion avoiding the previously typical partisan and worker's themes suddenly achieved huge cinematographic success. At the same time, it was also highly criticized, characterized as kitsch showing the 'deformation of contemporary life', 'something alien to our reality'. Critics were partially correct, the film was unrealistic, but only because it was a projection of a desired future which was supposed to be modern and urban, based on Westernized popular culture. Thus, the weak storyline was only a setting for a hundred-minute entertaining music video promoting modern and urban lifestyles in which the youth is following popular music and Western fashion trends, all combined with performances of the most popular Yugoslav singers like Gabi Novak or Ivo Robić. This article, through the example of Love and fashion, explores the role of popular music and its stars in the creation of a Yugoslav socialist dolce vita on screen.